Religious Paradox and Aporia (Nuntius Antiquus, 2018)
Focusing on religious or metaphysical paradox, which is, strangely, a neglected subject, this paper surveys well-known and little known instances in ancient Greek literature and early Christian sources. Religious paradox is highlighted in texts ranging from Hesiod, Archilochus, Heraclitus, and Euripides’ Bacchae to the Gospel of St John, St Paul, and the 6th century Akathistos Hymnos in honour of the Virgin Mary. Aporia in the wake of religious paradox confirms human limitation and points to the transcendence of the divine. Christianity, the religion of paradox par excellence, acknowledges the impossibility of offering philosophical “solutions” to the paradoxes and aporiai of dogma, and resorts to oxymoron and paradox as the only adequate form of expression. The only recourse before the estranging dislocation of order and logic provoked by contact with the divine is “ignorance”, for paradoxically ἐν ἀγνοίᾳ γὰρ γίνεται γνωστὸς ὁ Θεός (“God becomes known/knowable through ignorance”), as St Dionysius the Areopagite states.